2021
DOI: 10.1016/j.tust.2020.103661
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation on the maximum temperature and smoke back-layering length in a tilted tunnel under natural ventilation

Abstract: The present study investigates the maximum temperature and smoke back-layering length S in the downhill direction from the fire source in a tilted tunnel under natural ventilation. Numerical simulations were conducted using FDS to study the smoke flow behaviors for a fire in a tunnel with nine tunnel slopes of 0, 1%, 2%, 3%, 4%, 5%, 6%, 7% and 8%. It was found that, due to the stack effect, the smoke stagnated at a distance from the fire source in the downhill direction. The effects of tunnel slope,  , fire s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Zhang et al 23 carried out the numerical simulation under natural smoke exhaust system without the vertical shaft in a tilted tunnel and proposed an expression of the smoke back-layering length as equation (2)where S is the smoke back-layering length (m). α is the tunnel slope (%).…”
Section: Theoretical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al 23 carried out the numerical simulation under natural smoke exhaust system without the vertical shaft in a tilted tunnel and proposed an expression of the smoke back-layering length as equation (2)where S is the smoke back-layering length (m). α is the tunnel slope (%).…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Wan et al 22 proposed a model of the inlet air velocity of fires in an inclined tunnel under natural ventilation with a vertical shaft by dimensional analysis and numerical study. Zhang et al 23 conducted numerical simulation and dimensional analysis to establish a model of the smoke back-layering length that is independent of the heat release rate. Kong et al 24 carried out numerical simulations and theoretical analysis to analyze the effect of the different longitudinal fire locations on smoke behaviour characteristics caused by fires in inclined tunnels.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Alpert [ 8 ] and Kurioka et al [ 9 ] developed maximum temperature prediction models for a tunnel fire. Moreover, researchers have carried out studies on the factors affecting the maximum temperature, such as the location and number of fire sources [ 10 12 ], the shape of tunnel cross-section [ 13 , 14 ], velocity of longitudinal ventilation [ 15 ], vehicle blockage in a tunnel [ 16 , 17 ], ambient pressure [ 18 , 19 ], and the slope of the vertical shaft [ 20 ]. In addition to the maximum temperature, researchers have also investigated temperature decay.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been shown in previous studies that the temperature in a tunnel fire can be affected by various aspects, such as the tunnel geometry, inclination, location of fires, ventilation conditions, vehicle blockage, etc. [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [13] revealed that the maximum temperature below the tunnel ceiling varies with the tunnel slope. Their results showed that an increase in the tunnel slope decreases the maximum temperature.…”
Section: Introductionmentioning
confidence: 99%